2017
DOI: 10.1155/2017/9829436
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Levels and Their Relation to Clinical Features in Patients with Autoimmune Liver Diseases

Abstract: Serum cytokine levels were explored in a combined group of patients with autoimmune liver diseases (AILDs) and separately in patients with autoimmune hepatitis (AIH) and overlap syndrome. Overall, 60 patients with AILD, among them 32 patients with AIH and 28 patients with overlap syndrome, were included in the cross-sectional study. Serum cytokine levels were measured at baseline and compared to those of 21 healthy controls. Patients with AILD had significantly higher levels of IL-6 (0.70 (range 0.17–99.86) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
2
20
1
1
Order By: Relevance
“…We then investigated the mechanisms involved in BMDCs maturation in EAH model, which is the recognized animal model of AIH. Accumulating evidence has shown that, in AIH patients and EAH model, the serum levels of LPS, TNF-α and IL-33 were markedly increased compared with that in healthy controls [22][23][24] . To reveal whether those elevated cytokines in AIH patients or EAH model could induce the maturation of BMDCs, im-BMDCs were stimulated in vitro with LPS, TNF-α and IL-33, respectively.…”
Section: Cona Trigger Phenotypic Characteristics Of Bmdcs By Aberrantmentioning
confidence: 97%
“…We then investigated the mechanisms involved in BMDCs maturation in EAH model, which is the recognized animal model of AIH. Accumulating evidence has shown that, in AIH patients and EAH model, the serum levels of LPS, TNF-α and IL-33 were markedly increased compared with that in healthy controls [22][23][24] . To reveal whether those elevated cytokines in AIH patients or EAH model could induce the maturation of BMDCs, im-BMDCs were stimulated in vitro with LPS, TNF-α and IL-33, respectively.…”
Section: Cona Trigger Phenotypic Characteristics Of Bmdcs By Aberrantmentioning
confidence: 97%
“…Therapy monitoring of human autoimmune diseases has identified several measurable blood and serum biomarkers which correlate with immune activity (Table 3). In autoimmunity, the used biomarkers vary depending on the kind of autoimmune disease reflecting different immunologic response mechanisms [25][26][27][28][29]. Therefore, in the presented study a panel of different biomarkers suggesting immune activation has been screened retrospectively for a temporal association with either the release of cancer-derived proteins in the serum or the rise of proteins from tissues which have been damaged by checkpoint inhibitor-induced inflammation.…”
Section: Biomarker Cancer Entitymentioning
confidence: 99%
“…This approach has been tested for melanoma checkpoint inhibitor treatment in order to provide proof of principle, but it could represent a universal algorithm which might also be applicable to other cancer entities. [27,28] Peripheral blood count: elevated eosinophils Autoimmune pneumonitis [29] The next paragraph deals with theoretical considerations on the choice of biomarkers for detection of immune activation as well as for monitoring tissue damage of cancer cells and of organs targeted by immune-mediated side effects.…”
Section: Biomarker Cancer Entitymentioning
confidence: 99%
“…Вариантные формы различных заболеваний печени аутоиммунной этиологии (АИГ, ПБХ, ПСХ) называют синдромом перекреста. Обсуждаются их патофизиологические механизмы: случайное совпадение двух независимых аутоиммунных заболеваний или наличие у одного пациента одновременно двух аутоиммунных заболеваний [2,[19][20][21]. Сопутствующее заболевание печени усложняет диагностику и лечение АИГ [2].…”
Section: клиническая картина аутоиммунного гепатитаunclassified